CURRENT CONCEPTS IN THE MANAGEMENT OF KNEE OSTEOARTHRITIS: BIO-LOGIC THERAPIES IN FOCUS — A NARRATIVE REVIEW - Maksymilian Szombara,; Amin Omidi,; Maja Ćwiek,; Klaudia Malec,; Bartosz Krawiec,; Bartłomiej Zarębski,; Olaf Jadanowski,; Jakub Sójka,; Michał Mokrzyński,; Piotr Szyszka, (International Journal of Innovative Technologies in Social Science, 2025)
Knee osteoarthritis (KOA) is the most common form of degenerative joint disease and a lead-ing cause of disability worldwide. It is characterized by progressive cartilage degradation, sub-chondral bone remodeling, synovial inflammation, and chronic pain, which together lead to significant functional impairment and reduced quality of life. The global prevalence of KOA is rising in parallel with aging populations and increasing obesity rates, posing a substantial soci-oeconomic burden.In recent years, growing attention has been directed toward biological therapies, which aim to modify disease progression rather than only alleviate symptoms. This narrative review summa-rizes current evidence on the use of platelet-rich plasma (PRP), hyaluronic acid (HA), and mes-enchymal stem/stromal cells (MSCs) for KOA, as well as emerging combination strategies. Literature was identified through PubMed and Scopus searches focusing on randomized trials, systematic reviews, and guideline statements.Overall, PRP injections demonstrate superior short- to mid-term outcomes compared with HA in pain relief and functional scores, though results vary with preparation methods. HA remains widely used, particularly in early disease, but provides modest benefits. MSC therapies show promise in structural modification and long-term symptom improvement, though heterogeneity of protocols and limited high-quality trials restrict definitive conclusions. Combination and next-generation biologic approaches are under active investigation.In conclusion, biological therapies represent a rapidly evolving frontier in KOA management. While evidence supports meaningful clinical benefit of PRP and potentially MSCs, lack of standardized protocols and robust long-term trials remain major limitations. Future research should focus on optimization, safety, cost-effectiveness, and integration into clinical guide-lines.